CAUSATIVE CONSTRUCTION IN ASAHAN MALAY LANGUAGE: MORPHOLOGICAL CAUSATIVE ANALYSIS - Muhammad Yusuf; Mulyadi Mulyadi (Universitas Bengkulu, 2021)
This study attempts to describe morphological causative in Asahan Malay Language (AML). This research employed qualitative approach. This study followed the steps of data collection and data analysis. The data of this research were obtained through field linguistics method which covered direct elicitation, recording, and elicitation checking. The classified data were clarified with the native speakers of this language to improve the reliability of the data. From the analysis, it can be concluded that morphological causative construction in AML implies that the meaning of cause and effect. It is indicated by the use of suffix –kan and -i. In addition, causative markers of –kan and –i in AML can be attached to verbs, adjectives, nouns, and numerals.